Potential for Mesopelagic Fishery Compared to Economy and Fisheries Dynamics in Current Large Scale Danish Pelagic Fishery - Paoletti, Silvia; Nielsen, J. Rasmus; Sparrevohn, Claus R.; Bastardie, Francois; Vastenhoud, Berthe M. J. (Frontiers in Marine Science, 2021)
Mesopelagic fish species represent a large potentially unexploited resource for the fishing industry and the fish meal, oil, nutraceutical and pharmaceutical production. However, thorough investigation on ecological sustainability and socio-economic viability are fundamental prerequisites for potential exploitation. The current study explores the economic viability of a potential mesopelagic fishery investigating minimum catch rates, under the assumption of previous assessments of biological sustainability of such exploitation. We analysed fishery data from the North-East Atlantic fisheries of the Danish large pelagic fleet from 2015 to 2019 and compared and combined the fishing dynamics and cost-structures with data from interviews of key pelagic producer organization representatives to develop scenarios of profitability. The results show full year-round fleet occupation with the ongoing fisheries, exposing the need of switching from existing activities, or investing into new vessels for conducting potential mesopelagic fishery. Economic analyses revealed that the minimum revenue to break even (zero profit) by trip varies among métiers between 60’000 to 200’000 euro showing strong positive correlation with vessel sizes. High profitability was discovered for herring, Atlantic mackerel and blue whiting fisheries while low profitability was observed for the Norway pout fishery. Due to the lack of mesopelagic fishery data, different scenarios of profitability were investigated as informed by the pelagic catch sector stakeholder perceptions of prices and costs and compared to current economic dynamics. A high break-even revenue per trip was forecasted given the increased perceived costs for fuel, modifications of gears and on-board processing methods and potential new vessel investments. High profitability may be reached if the catches exceed 220-1060 tonnes per trip depending on costs and vessel storage capacity. If the conservation methods are improved from current refrigerated sea water, fishing trips could last longer than 5 days, being the major limiting economic factor for potential mesopelagic fishery. Future investigations on realistic mesopelagic catches, trip durations and spatio-temporal distribution of fisheries in relation to location, resource abundance, fishing rights, storage and conservation methods will be essential to test the robustness of the scenarios proposed in this study, and will in turn benefit of the economic requirements evaluated herein.